How dark is the night sky? A preliminary assessment of light pollution and astrotourism potential - Danny Firmansyah; Yaumil Khairin Septiani; Ilham Ramdhani; Nur Fadhillah; Winny Liliawati; Cahyo Puji Asmoro (The Journal of City: Branding and Authenticity, 2026)
Background: Light pollution degrades night sky quality and may limit opportunities for astronomy-based tourism (astrotourism). Although Batu City has astrotourism potential, information on its night sky quality remains limited. This study characterized night sky brightness in Batu District, compared field measurements with Light Pollution Map (LPM) data, and evaluated its implications for astrotourism. Methods: Night sky brightness was measured at six observation sites in Batu District using a D.I.Y-CJ'01 photometer equipped with a TSL237 sensor. Measurements were conducted at the zenith under suitable weather conditions for 2–3 minutes at each site. Data were expressed in mag/arcsec², classified using the Bortle Scale, and compared with LPM data. Findings: The average night sky brightness ranged from 11.81 to 18.10 mag/arcsec². The highest value occurred in a peripheral residential area and the lowest in a commercial area. Most sites were classified as Bortle Class VIII–IX, indicating city to inner-city sky conditions. LPM estimated darker skies (19.79–20.46 mag/arcsec²; Bortle Class IV–V) than field measurements, although both showed decreasing sky quality with increasing urban activity and artificial lighting. However, the findings should be interpreted with caution because of methodological limitations, including measurement duration, technical limitations of the instrument, differences between photometer and LPM measurements, and uncontrolled environmental factors. Conclusion: The results indicate substantial light pollution in Batu District, making most surveyed locations less suitable for astrotourism. However, variations in sky brightness suggest that other areas of Batu City may still support astrotourism. These findings are expected to guide regional planners and tourism stakeholders in formulating artificial lighting management policies that support the sustainable development of astrotourism in Batu City. Novelty/Originality of this article: This study provides a preliminary field-based assessment of night sky brightness, light pollution, and astrotourism potential in Batu District through direct photometric measurements and LPM comparison.